Formation of emerging disinfection by-products by chlorination/chloramination of seawater impacted by algal organic matter - Nihemaiti, M.; Roux, J.; Croue, Jean-Philippe (Springer Int.Publising, 2015)
The aim of this work was to study the formation of haloacetamides (HAcAms) and other DBPs during chlorination and chloramination of algal organic matter (AlOM). The HAcAms formation potentials of different precursors (amino acids, simulated algal blooms grown in the Red Sea) were evaluated. Experiments with simulated algal blooms were conducted in the presence of bromide ion (synthetic seawater containing 800 µg/L Br) to assess the formation of brominated analogues of HAcAms in conditions close to the disinfection of real seawater. Chlorination produced more HAcAms than chloramination from real algae (Synecococcus sp.), thus indicating that the nitrogen of HAcAms comes predominantly from DON through the decarboxylation of amino acids rather than from NH2Cl. Dibrominated species of DBPs (i.e., DBAcAm, DBAA and DBAN) were the dominant species formed by both chlorination and chloramination of algal bloom samples. Chloramination of the amino acid asparagine produced an important amount of DCAcAm as compared to chlorination, indicating the existence of a specific reaction pathway.